Upregulation of METTL3 expression and m6A RNA methylation in placental trophoblasts in preeclampsia. (1st January 2021) - Gu, Yang; Chu, Xiaodan; Morgan, John A.; Lewis, David F.; Wang, Yuping
Abstract: Introduction: N6-methyladenosine (m6A) has been recognized as one of the most abundant and functionally relevant modifications of RNAs and plays critical roles in biological and pathological processes. Placental trophoblast dysfunction significantly contributes to the pathogenesis of preeclampsia. The present study aimed to determine if altered m6A expression occurs in placental trophoblasts in preeclampsia. Expression of m6A methyltransferase (methyltransferase like 3 (METTL3)), m6A demethylases (fat mass and obesity-associated protein (FTO) and AlkB homolog 5 (ALKBH5)), and m6A reader protein, heterogeneous nuclear ribonucleoprotein C1/C2 (hnRNPC1/C2), were also examined. Methods: A total of 43 placentas (20 normal term, 5 normotensive preterm, and 18 preeclamptic) were used in the study. Expression of m6A, METTL3, FTO, ALKBH5, and hnRNPC1/C2 were examined by immunostaining in villous tissue sections and/or by Western blot of total cellular protein in trophoblasts isolated from normotensive and preeclamptic placentas. Total RNA extracted from trophoblasts was used to measure m6A RNA methylation. Effects of METTL3 on m6A RNA methylation and hnRNPC1/C2 expression were assessed by transfection of METTL3 siRNA in trophoblasts from preeclamptic placentas. Results: Expression of m6A and m6A RNA methylation were significantly increased in trophoblasts from preeclamptic vs. normotensive placentas, p < 0.05. Expression of METTL3 and hnRNPC1/C2, but not FTO and ALKBH5, was significantly upregulated in trophoblasts from preeclamptic vs. normotensive placentas, p < 0.01. Transfection of METTL3 siRNA significantly reduced the level of m6A RNA methylation and hnRNPC1/C2 expression in trophoblasts from preeclamptic placentas, p < 0.05. Conclusion: The finding of increased METTL3 expression and m6A RNA methylation associated with increased hnRNPC1/C2 expression provides a new posttranscriptional mechanism that aberrant m6A modification may contribute to trophoblast dysfunction in preeclampsia. Highlights: m6A expression and m6A RNA methylation were increased in trophoblasts (TCs) from preeclamptic (PE) vs. normal placentas. Expression of m6A methyltransferase METTL3 and m6A reader protein hnRNPC1/C2 were increased in PE TCs vs. normal TCs. TC expression of m6A demethylases FTO and ALKBH5 was not different between normal and PE placentas. Inhibition of METTL3 expression downregulated m6A RNA methylation and hnRNPC1/C2 expression in TCs from PE placentas.